RETRACTED ARTICLE: Health-related quality of life among ethnic minority residents in remote Western China: a cross-sectional study - Jiaxin Dong; Xiaoju Li; Rong Fan; Jielin Yang (BMC, 2023)
Abstract Background Paying attention to the health-related quality of life (HRQOL) of rural residents in poverty-stricken areas is an important part of China's poverty alleviation, but most studies on health-related quality of life have focused on rural residents, elderly individuals, and patients; evidence on the HRQOL of rural minority residents is limited. Thus, this study aimed to assess the HRQOL of rural Uighur residents in remote areas of Xinjiang, China, and determine its influencing factors to provide policy opinions for realizing a healthy China strategy. Methods A cross-sectional study was performed on 1019 Uighur residents in rural areas. The EQ-5D and self-administered questionnaires were used to assess HRQOL. We applied Tobit and binary logit regression models to analyse the factors influencing HRQOL among rural Uighur residents. Results The health utility index of the 1019 residents was − 0.197,1. The highest proportion of respondents reporting any problem was for mobility (57.5%), followed by usual activity (52.8%). Low levels of the five dimensions were related to age, smoking, sleep time, Daily intake of vegetables and fruit per capita. Gender, age, marital status, physical exercise, sleep duration, daily intake of cooking oil per capita, daily intake of fruit per capita, distance to the nearest medical institution, non-infectious chronic diseases (NCDs), self-rated health score, and participation in community activities were correlated with the health utility index of rural Uighur residents. Conclusions HRQOL was lower for rural Uyghur residents than for the general population. Improving health behavioural lifestyles and reducing the incidence of poverty (return to poverty) due to illness are effective means of promoting the health in Uyghur residents. The region must fulfil the health poverty alleviation policy and focus on vulnerable groups and low-income residents to improve the health, ability, opportunity, and confidence of this population to live well.